2017
DOI: 10.1002/job.2238
|View full text |Cite
|
Sign up to set email alerts
|

When can culturally diverse teams be more creative? The role of leaders' benevolent paternalism

Abstract: The current research examines the conditions under which cross-cultural teams can realize their creative potential-a consequence of their cultural diversity. We propose that in more culturally diverse teams, team members are less open when communicating with each other, which impairs the team's ability to elaborate on the information contributed by different members, ultimately limiting team creativity. We further theorize that leaders' benevolent paternalism, a leadership style that is particularly prevalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 99 publications
(117 reference statements)
4
29
0
Order By: Relevance
“…We specified a single‐factor, a two‐factor, and our hypothesized five‐factor solution for a two‐level CFA to generate unbiased estimates of the group‐level factor structure by statistically accounting for the within‐group factor structure (Hox, ). The factor loadings of the first indicator of a latent variable were set to one to fix the scale of the latent variable, the error terms were modeled independently, and cross‐loadings were not estimated (Huang, ; Lu, Li, Leung, Savani, & Morris, ). All the parameter estimates for the factor loading from the five latent variables to their respective observed indicators were significant on the between and the within level.…”
Section: Analysesmentioning
confidence: 99%
“…We specified a single‐factor, a two‐factor, and our hypothesized five‐factor solution for a two‐level CFA to generate unbiased estimates of the group‐level factor structure by statistically accounting for the within‐group factor structure (Hox, ). The factor loadings of the first indicator of a latent variable were set to one to fix the scale of the latent variable, the error terms were modeled independently, and cross‐loadings were not estimated (Huang, ; Lu, Li, Leung, Savani, & Morris, ). All the parameter estimates for the factor loading from the five latent variables to their respective observed indicators were significant on the between and the within level.…”
Section: Analysesmentioning
confidence: 99%
“…The results of the hypothesis 1 are in line with the previous findings (Walumbwa & Schaubroeck, 2009;Bienefeld & Grote, 2014a) suggesting that role of leadership is one of the key features affecting employees' psychological safety. When employees have paternalistic leader around them, they feel safer psychologically because benevolent leaders try to create familial culture for the employees to interact in a team and to have more sense of psychological safety (Lu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Detert and Burris (2007) also concluded that the leader who is more into inspirational motivation and is more considerate towards the individual employees, enhances the psychological safety of the employees. Researchers have also explored that benevolent leaders have a significant impact on psychological safety (Edmondson, 1999;Erkutlu & Chafra, 2016;Lu, Li, Leung, Savani, & Morris, 2018;May, Gilson, & Harter, 2004). Research has also highlighted that good quality leadership is one that is consistent and important predictor of psychological safety (Barling, Akers, & Beiko, 2018;Nembhard & Edmondson;2006;Roussin & Webber, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Out of the articles pulled as a result of our literature search, the most common methodological tools during the team formation used was through the forms of self-reported survey questionnaires. For example, a study by Lu et al (2018) on openness, using a two-wave multi-source online survey with responses from 30 teams from different multicultural organizations in China, found that reduced openness hinders a diverse team’s ability to generate innovative solutions. Especially in diverse teams, a lack of communication openness can have an impairing impact on team member information elaboration and creativity, later on.…”
Section: Role Of Team Dynamics In Team Developmentmentioning
confidence: 99%